Pelatihan Birth Ball Pada Ibu Hamil Dalam Upaya Menurunkan Nyeri Persalinan - Apri Sulistianingsih; Istikomah Istikomah (Jurnal Empathy Pengabdian Kepada Masyarakat, 2022)
Background: Birth balls are common among mothers giving birth, but mothers who know them for the first time are generally afraid to use them. Training for pregnant women can increase their knowledge about the use of birth balls, and the mothers are skilled at the delivery time. This community service aims to train pregnant women to use birth balls to reduce labor pain. Methods: The form of activity is birth ball training for pregnant women to reduce labor pain in Sumberrejo Pringsewu Village. The activity is carried out in January 2022 every Tuesday, and we are at 09.00 WIB until it is finished. The target of this community service is 30 pregnant women. The service team and the Village Midwife work together to arrange the activities schedule and the birth ball training implementation. Results: pregnant women's skills in using birth balls before service was 52.19 (6.33), then increased after service to 84.4 (2.71). Statistical tests show that community service activities for pregnant women effectively improve mothers' skills using birth balls in pain management. Conclusion: This skill improvement is important for pregnant women so that pregnant women are accustomed to using a birth ball during delivery. Mothers are also proficient in doing movements using a birth ball which helps reduce pain, and the duration of labor becomes faster.